Inisiatif Damai di Asia Tenggara: Pelajaran dari Peran Catholic Relief Services dan Muhammadiyah Dalam Peace Building di Timor-Leste and Mindanao - Sugito; Reynaldi , Hendy Achmad; Mas'udi, Syasya Yuania Fadila; Ahmadi, Sidiq (Jurnal Ilmiah Hubungan Internasional, 2025)
This study of international non-governmental actors (INGO) and peacebuilding has sparked a lively discussion because INGOs play a significant role in the peace process. On the other hand, INGOs with their own values frequently fight with one another or with the values of the local community. This study tries to comprehend the peacebuilding strategies of The Catholic Relief Service (CRS) and Muhammadiyah in conflict zones, particularly Timor-Leste and Mindanao. This study employs a qualitative approach with document analysis. The findings of this study indicate that CRS and Muhammadiyah play a significant role in promoting peace through the following efforts: (1) reducing human suffering by seeking the safety of conflict victims; (2) promoting peace through a democratic, non-violent, and participatory process by focusing on the safety of women and other vulnerable people; and (3) post-conflict reconstruction by restoring the lives of people affected by conflict in various aspects.